Phase angle derived from bioelectrical impedance analysis as a marker for predicting sarcopenia - Wu, Haotian; Ding, Ping'an; Wu, Jiaxiang; Yang, Peigang; Tian, Yuan; Zhao, Qun (Frontiers in Nutrition, 2022)
It is well known that sarcopenia is commonly defined as age-related loss of muscle mass and function which may caused by a number of factors, including genetic factors, environmental condition, lifestyle, drug use and especially comorbidities. People suffer from diseases are more likely to develop sarcopenia, which may have adversely impact on the prognosis. Resently, phase angle (PhA) which derived from bioelectrical impedance analysis (BIA) have received extensive attention, and numerous studies have done to prove the relationship between the PhA and sarcopenia in different conditions. Based on these studies, we are expecting that PhA could be used as potential marker for sarcopenia in the future.